Proxemics study on active engagement of filipino junior high school students establishing design guidelines for sociopetal and sociofugal spaces in an academic environment - Enano, Cserah Marl G.; Olalo, Kristin Faye M. (2019)
The study aims to determine the active engagement factors that dictate the proxemics properties of a Filipino junior high school age group in orderto address a learner's wide array of affective, behavioral and cognitive active engagement characteristics. Through a Participatory Research Method, the results had shown that personality is a significant predictor of distance. Orientation encompasses the learning modalities, personality, and age as its significant factors. Age, learning modalities is a predictor of enclosure while gender and personality is for formation. The study extensively explored the underlying variables that had generated such results, and found out 6 factors that influence the behavioral arrangement of the learners namely: (1) Social Exhaustion, (2) Comprehensive Listening, (3) Emphatic Listening, (4) Visual Processing Sensitivity, (5) Spatial Permeability and (6) Expressiveness. These factors contribute to the space patterns of the students that needs to be addressed through provision of facilities and areasthat consider and stimulate their dominant tendencies. Thestudy indicates the necessity of reconfiguring the standard present-dayschool set-upin order to pave way for a more user centered environment and to provides an in depth detail in understanding the space behavior of junior high school learners.
Thesis(BS Architecture)--University of the Philippines Mindanao, 2019